An Assessment of the Implications of Executive Orders 21 and 22 for the 2023 General Elections in Rivers State, Nigeria - Nweke, Kenneth; Nwankwo, Evans O. (University of Nigeria Journal of Political Economy, 2023)
This paper assesses the implications of Executive Orders 21 and 22 for the 2023 general elections in Rivers State, Nigeria. The paper opined that Executive Orders derive from existing laws but it is not the case with the Rivers State Executive Orders 21 and 22. The paper argued that the Executive Orders 21 and 22 are designed to grandstand and stifle opposition and the people from freely engaging in competitive political contestations in the build-up to the 2023 general elections in Rivers State. The paper adopted the legalist theory to interrogate the constitutionality of the Executive Orders 21 and 22 as they run contrary to the provisions of the Constitution of the Federal Republic of Nigeria, 1999 (As amended) and other extant electoral laws within the confines of exclusive powers of the National Assembly. Sources of data are both primary and secondary and the methods of data analysis are descriptive and content analytic models, respectively. The paper concluded that implementing the Executive Orders 21 and 22 would negatively affect the 2023 general elections in Rivers State, hence a recipe for political violence and voter apathy in a State perceived to have been polarised along ethnic and party lines, and consequently conquered for certain selfish political interests. The paper recommended among others, that the opposition and Civil Society Organisations should challenge the legality of the Orders in Court to act as a deterrence to successive State Chief Executives with a view to ensuring a level-playing field for all not just for the 2023 but future general elections in Rivers State.